The effect of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) on mice myocardial morphology - Sasahara, Tais H.C.; Machado, Marcia R.F. [UNESP] (FapUNIFESP (SciELO), 2019)
Studies have demonstrated sympathetic cardiac denervation in the MPTP mouse model. MPTP toxicity causes sympathetic nerve damage and depletion of heart norepinephrine. Previous evaluations of impairments in heart innervation have been based on imaging, electrophysiological and biochemical methods. However, these studies lacked information that can be obtained from morphoquantitative analyses. Thus, this study aimed to apply a design-based stereological method for evaluating the morphoquantitative alterations of myocardium following treatment with the neurotoxin MPTP in the C57/BL mouse. Our results showed that MPTP reduced the number of cardiomyocytes in the left ventricle.
O efeito do 1-metil-4-fenil-1,2,3,6 tetrahidropiridina (MPTP) na morfologia do miocárdio de camundongo